In Silico Identification And Comparison Of Surface Binding Pockets Of Vibrio Parahaemolyticus Thermostable Direct Hemolysin Proteins - MALATHI SHEKAR; IDDYA KARUNASAGAR; INDRANI KARUNASAGAR (International Journal of Pharma and Bio Sciences, 2012)
V.parahaemolyticus pathogenicity has been associated with its ability to produce thermostable direct hemolysin (TDH) encoded by the tdh gene. Although all V.parahaemolyticus strains possess this gene some strains are hemolytic, intermediate or non-hemolytic. To assess the differences seen, we screened the surface of the TDH proteins showing variable hemolytic activity for identification of possible pockets/cavities. We report here the probable large binding pockets associated with TDH, the key residues involved in their formation and their physicochemical parameters. Several ‘hotspot’ residues associated with binding sites identified are also reported. This report is the first to study the surface of the TDH protein, the results of which could be used in planning experiments for further understanding the way the protein expresses and interacts.